2017
DOI: 10.1016/j.stemcr.2017.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenic Identification and Analysis of Mesenchymal Stromal Cell Populations during Mouse Limb and Long Bone Development

Abstract: SummaryBone-derived mesenchymal stromal cells (MSCs) differentiate into multiple lineages including chondro- and osteogenic fates and function in establishing the hematopoietic compartment of the bone marrow. Here, we analyze the emergence of different MSC types during mouse limb and long bone development. In particular, PDGFRαposSCA-1pos (PαS) cells and mouse skeletal stem cells (mSSCs) are detected within the PDGFRαposCD51pos (PαCD51) mesenchymal progenitors, which are the most abundant progenitors in early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 48 publications
(98 reference statements)
0
30
0
Order By: Relevance
“…Previous analysis of limb bud mesenchymal cells had established that the vast majority express platelet-derived growth factor receptor α (PDGFRα; Takakura et al, 1997), which, in combination with SCA-1, allowed FACS-mediated isolation of mesenchymal stromal cells (MSCs) during limb long bone development (Morikawa et al, 2009; Craft et al, 2013; Nusspaumer et al, 2017). To gain insight into the potentially cellular heterogeneity during the early phase of forelimb bud outgrowth, we used mouse embryos at E10.5-E10.75 (35-38 somites, Figs 2–7).…”
Section: Resultsmentioning
confidence: 99%
“…Previous analysis of limb bud mesenchymal cells had established that the vast majority express platelet-derived growth factor receptor α (PDGFRα; Takakura et al, 1997), which, in combination with SCA-1, allowed FACS-mediated isolation of mesenchymal stromal cells (MSCs) during limb long bone development (Morikawa et al, 2009; Craft et al, 2013; Nusspaumer et al, 2017). To gain insight into the potentially cellular heterogeneity during the early phase of forelimb bud outgrowth, we used mouse embryos at E10.5-E10.75 (35-38 somites, Figs 2–7).…”
Section: Resultsmentioning
confidence: 99%
“…We exploit cell-specific molecular fingerprints to infer relevant unknown functional aspects and unequivocally trace the anatomical localization of PαSc. Originally defined as a population enriched in mesenchymal stem cell potential, this cell type has been mostly investigated through the use of in vitro cultures, orthotopic or systemic transplantation (Hu et al, 2016;Nusspaumer et al, 2017), and their principal biological features remain undefined. We unexpectedly observed that PαSc express a signature associated to pre-chondrogenic potential, which stands in contrast to the strong osteoblastic 15 and adipogenic signatures of CARc.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, PDGFR-α + Sca-1 + (here designated PαSc) were initially described on the basis of a phenotypic signature that uniquely differs from that of CARc on the expression of Sca-1 (Morikawa et al, 2009). Flow cytometry studies have shown that PαS cells are found at highest frequencies in developing bone, but gradually decline to represent a very low fraction of the mesenchymal compartment in adult BM (Hu et al, 2016;Nusspaumer et al, 2017). Both CARc and PαSc contain CFU-F potential, trilineage differentiation capabilities in vitro, and give rise to osteoblasts, reticular stroma and adipocytes in vivo (Morikawa et al, 2009;Omatsu et al, 2010).…”
mentioning
confidence: 99%
“…We next assessed whether the plasticity of EMT-derived breast cancer cells includes the ability to differentiate into further cell types of the mesenchymal lineage, such as osteoblasts and chondrocytes, as previously demonstrated for non-transformed cells (Battula et al, 2010). MTDECad cells were treated with differentiation protocols adapted from a previous report on the induction of osteogenesis and chondrogenesis (Nusspaumer et al, 2017). Indeed, osteogenesis-induced cells expressed the osteoblast regulator Osterix ( Figure S1B), while chondrogenesis-induced cells expressed chondrocyte-specific collagen type 2 and Sox9, a master transcription factor of chondrogenesis ( Figure S1C).…”
Section: Emt Breast Cancer Cells Trans-differentiate Into Adipocytesmentioning
confidence: 99%